Effects of fabrication sequence annealing and deposition electrode on the performance of inverted polymer solar cells - Cao, Qi (2011)
As the amount of fossil fuel is continuously decreasing and burning of traditional fuel brings severe environmental problems, solar energy, as an inexpensive alternative for renewable energy, has been continuously attracting attention. This project aims to explore the effect of the fabrication sequence of annealing and deposition electrode on the performance and degradation process of inverted polymer solar cells. In this project, two sets of inverted polymer solar cells in which the photoactive layer was annealed before and after top electrode deposition were fabricated respectively. The performance of devices was characterized under illumination of 100 mW/cm2 AM 1.5G. Photovoltaic parameters of devices, such as open-circuit voltage, short-circuit current, fill factor and power conversion efficiency were extracted and analyzed at different time. The relationship between the device fabrication sequence and the performance, the stability of devices were investigated. The results show that the performance and stability of devices which the photoactive layer was annealed after top electrode deposition is better than that of devices which photoactive layer was annealed before top electrode deposition. Two sets of devices also show different behaviors under longtime sun illumination, which related to the filling defect of ZnO nanoparticle layer under illumination and the oxygen penetration from the electrode into the organic photoactive layer. To study the influences of sequence of annealing photoactive layer on structure, the performance and stability of devices, the scanning electron microscope was conducted. The SEM results show the phase separation of p and n type semiconductor in photoactive layer and the surface morphologies strongly depends on the fabrication sequence of devices, thus lead to different performance and stability. The elucidation of relationships between processing with structure and performance could eventually lead to better understand the device operation and guide to improve the performance and stability of devices.